If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8z-2=-9z-4+1
We move all terms to the left:
-8z-2-(-9z-4+1)=0
We add all the numbers together, and all the variables
-8z-(-9z-3)-2=0
We get rid of parentheses
-8z+9z+3-2=0
We add all the numbers together, and all the variables
z+1=0
We move all terms containing z to the left, all other terms to the right
z=-1
| 11=8s+47 | | 4m2-m=0 | | -90=-3(2-+x) | | 3(x-2)+7x-3=-32 | | 3x-11+6x+10=180 | | 4x-21=8x45 | | e+5=1 | | -1-7m=-6m-10 | | 9x-5=1/4(16x+20) | | N=-50p+2000 | | 12x–20=64 | | 98=7(j+2) | | 4(x-9)^2-15=25 | | 8x–2=30 | | -w-4=2-2w | | 7v–3=25 | | c-6=2 | | -4(-7x+5)+4x=-244 | | f=144−8 | | 10(y+4)−3=14y+1 | | 4(3y+2)=4(2y+3)+4y | | (16x+x)x=90 | | 5+7x^2=90.75 | | -8+6(-5x+7)=214 | | 15-x=6;x= | | 9v-10=10=3v+10 | | 2+4v-9)=14 | | 4(w+36)+4w=488 | | 3x–7=38 | | 9v-10=10+3v=+10 | | 5/y=7/36 | | c+51=96 |